1995
DOI: 10.1006/abbi.1995.1410
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of B-Ring-Deoxy Flavonoid Biosynthesis in Elicited Cell Cultures of "Old Man" Cactus (Cephalocereus senilis)

Abstract: Elicited cell cultures of the cactus Cephalocereus senilis produce a group of flavonoids with unsubstituted B-rings, including an aurone which represents a new class of phytoalexin. Preliminary enzymological studies indicated that the chalcone synthase (CHS) and chalcone isomerase (CHI) from cultures of C. senilis were active with cinnamoyl-CoA and 2',4',6'-trihydroxychalcone, respectively, probable intermediates for synthesis of flavonoids with unsubstituted B-rings. We now demonstrate that the cultures conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A broad-specificity 4CL activity supporting deoxyflavonoid biosynthesis was described in C . senilis ( 30 ), suggesting that a pathway different from the one we have characterized in S . baicalensis operates in this widely diverged species.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A broad-specificity 4CL activity supporting deoxyflavonoid biosynthesis was described in C . senilis ( 30 ), suggesting that a pathway different from the one we have characterized in S . baicalensis operates in this widely diverged species.…”
Section: Discussionmentioning
confidence: 71%
“…benthamiana showed that SbCLL-7 can compete with the endogenous C4H activity for cinnamic acid, an activity hypothesized, but not found, in old man’s cactus ( Cephalcereus senilis ) by Liu et al . ( 30 ). Indeed, transcript levels of C4H were particularly high in the roots and stems of Scutellaria (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some pathways of phenylpropanoid biosynthesis can bypass the C4H reaction. These include 2-hydroxylation of cinnamic acid by chloroplastic cinnamate 2-hydroxylase (Gestetner and Conn, 1974), glucosylation of cinnamic acid by UDP glucose:trans-cinnamic acid glucosyltransferase (Shimizu and Kojima, 1984;Edwards et al, 1990), and the biosynthesis of B-ring deoxy-flavonoids such as baicalein via a coumarate CoA ligase isoform that is active with cinnamic acid (Liu et al, 1995). Lignin, flavonoid, and chlorogenic acid biosynthesis in tobacco might operate through the channeled PAL isoform.…”
Section: Consequences Of Pal Localization For Metabolic Channeling Inmentioning
confidence: 99%
“…Type I CHI could catalyze 6-hydrox-chalcone into (2S)-flavonoid or (2S)-5-desoxidation flavonoid. Type I CHI was found in most of plant species such as barley, rape, Arabidopsis, and rice (Liu et al 1995;Druka et al 2003). Type II CHI, which was mainly found in leguminous plants could catalyze both 6-hydrox-chalcone and 6-deoxidation-chalcone into (2S)-flavonoid or (2S)-5-desoxidation flavonoid.…”
Section: Introductionmentioning
confidence: 99%